LANGUAGE IN COMMUNICATION: DISCUSSING INDONESIAN GRAMMAR IN RIDWAN KAMIL’S INSTAGRAM PHOTO AND CAPTION UPLOADS - Ertinawati, Yuni; Azzahra, Risa; Aaqilah, Hanifa Zemi; Lutfi, Aprisa (Media Inovasi Pendidikan dan Publikasi, 2024)
The use of Indonesian is implemented as a medium of communication for the unity of the Indonesian state to facilitate daily interactions with each other. Good and correct use of Indonesian is important to make understanding easier for the person you are talking to. This research aims to find out the good and correct use of Indonesian and to study Indonesian grammar in depth as a reference in writing. The topic used as material for research was Ridwan Kamil’s upload of a photo along with a caption on one of his social media account (Instagram) on July 21st 2024. The method used in this research is a qualitative descriptive method by analyzing grammatical patterns on social media to obtain information. In the research carried out, errors in the use of Indonesian language and grammar were found, including the use of foreign languages, slang, non-standard words and the use of regional languages (Sundanese).